Cataract and Glaucoma Patients Before and After Surgical Treatment - Rajabov Hamid (Zien Journals, 2022)
This article provides thorough information about the condition of patients having eye diseases, before and after surgery. In this article additional suggestions for doctors what to do with cataract patients are explained with pertinent practices conducted.
Keywords: ophthalmological examination; treatment; health; emotional state